Land structure change and ecological effects under future development scenarios in Tarim River Basin, Central Asia - Yifeng Hou; Yaning Chen; Zhi Li; Yupeng Li; Fan Sun (Geography and Sustainability)
Soil and water matching in a land basin is important for securing land demand, alleviating human-land conflicts, and promoting sustainable development in the region. The Tarim River Basin (TRB) is the largest inland river basin in China and primarily sustains an agricultural economy centered around oases. This study employs the Patch-generating Land-Use Simulation (PLUS) model to forecast the changing patterns of land use across various future scenarios. The connection between land development and the ecological environment is examined through the lens of relative ecological value and ecological impact. The results indicate that: (1) From 1992 to 2020, the ecology of the basin showed an improving trend, with the area of new cropland increasing by 18,850.51 km2 at a growth rate of 56.13 %. Grassland area increased by 10,235.29 km2 and barren land area decreased by 20,597.29 km2. (2) Under the four tested scenarios of Natural Development, Cropland Conservation, Ecological Protection, and Urban Expansion (scenarios I–Ⅳ, respectively), the PLUS results for the year 2050 show an increase in cropland area of 12.69 % under Scenario Ⅱ, an increase in grassland area of 20,374.82 km2 under Scenario Ⅳ, and an increase in built-up land area of 1,105.57 km2 under Scenario Ⅲ. (3) A simulation of the basin’s ecology in 2050 shows a significant improvement trend under Scenario Ⅳ. Specifically, the development of a large amount of barren land into grassland and woodland has significant ecological benefits, with a contribution rate of 61.88 % to 70.18 %. This study provides a strong scientific foundation for future land management and ecological sustainable development in the TRB.